Palm Oil Farmers' Perceptions on the Use of Personal Protective Equipment (PPE) in Rantau Rasau District, Tanjung Jabung District, Jambi Province - Willia Novita Eka Rini; Budi Aswin (East Asian Journal of Multidisciplinary Research, 2023)
Perception is an important psychological aspect, perception is a form of process in which individuals learn something through their five senses. This study uses a qualitative descriptive method. The attitude of oil palm farmers towards the use of PPE has a positive response, Oil palm farmers assume they have a good interest in using PPE. However, based on the results of observations that carried out by researchers it is known that oil palm smallholders still do not use PPE completely. The results of interviews show that the experience of oil palm smallholders can influence farmers' perceptions of the use of PPE. Oil palm farmers have hopes that there will be assistance from the government in the provision of tools and materials necessary assistance and also training or counseling so that farmers can manage their plantations well and efficiently. The attitude of oil palm farmers towards the use of PPE has a positive response, respondents only know a few types of PPE so that farmers think that they have a good interest in using PPE while working. It was found that some farmers had experienced accidents while working. The farmers hoped that there would be assistance from the local or central government.